1891 Wis. Sess. Laws 61, ch. 23, § 3, pt. 28 - (:unkn) unknown (My University, 1891)
Authorized the city to prohibit or regulate the carrying of any pistol, slung shot, knuckles, bowie knife, dirk, or any other dangerous weapon and to confiscate and sell such weapons.
Keywords: CARRY